Biofilm-formation capability depends on environmental oxygen concentrations in Candida species. Issue 5 (May 2022) - Koshikawa, Takuro; Abe, Masahiro; Nagi, Minoru; Miyazaki, Yoshitsugu; Takemura, Hiromu
Abstract: Background: Although oxygen concentrations inside of the human body vary depending on organs or tissues, few reports describe the relationships between biofilm formation of Candida species and oxygen concentrations. In this study, we investigated the biofilm-forming capabilities of Candida species under various oxygen conditions. Methods: We evaluated the adhesion and biofilm formation of Candida albicans and C. tropicalis under aerobic, microaerobic (oxygen concentration 5%), or anaerobic conditions. We also examined how oxygen concentration affects adhesion/maturation by changing adhesion/maturation phase conditions. We used crystal violet assay to estimate the approximate biofilm size, performed microscopic observation of biofilm morphology, and evaluated adhesion-associated gene expression. Results: The adhered amount was relatively small except for a clinical strain of C. tropicalis . Our biofilm-formation analysis showed that C. albicans formed a higher-size biofilm under aerobic conditions, while C. tropicalis favored microaerobic conditions to form mature biofilms. Our microscopic observations were consistent with these biofilm-formation analysis results. In particular, C. tropicalis exhibited more hyphal formation under microaerobic conditions. By changing the adhesion/maturation phase conditions, we represented that C. albicans had favorable biofilm-formation capability under aerobic conditions, while C. tropicalis showed enhanced biofilm formation under microaerobic adhesion conditions. In good agreement with these results, the C. tropicalis adhesion-associated gene expression tended to be higher under microaerobic or anaerobic conditions. Conclusions: C. albicans favored aerobic conditions to form biofilms, whereas C. tropicalis showed higher biofilm-formation ability and promoted hyphal growth under microaerobic conditions. These results indicate that favorable oxygen conditions significantly differ for each Candida species.